Optimization of Microwave-Assisted Synthesis Method for N-doped Carbon Dots (CDs) from Citronella Grass Oil Distillation Solid Waste and Its Antifungal Properties - Linggadiputra, Jonathan; Elvina Dhiaul Iftitah (The Journal of Pure and Applied Chemistry Research, 2026)
Carbon dots (CDs) are promising materials with unique optical and chemical properties, although their synthesis often involves harsh conditions and extended processing times. Microwave-assisted synthesis (MAS) offers a more efficient approach, especially when using renewable carbon sources. Citronella grass, which commonly grown in Indonesia and used in essential oil production, provides a high-carbon-content distillation waste (CGSW) ideal for CD production. This research explores the synthesis optimization process of CGSW as a precursor for CDs, utilizing open-vessel MAS method with NaOH as a solvent. Optimal synthesis conditions were found to be 800 W of power with 0.20 g of N-doping. The resulting CCDs has high quantum yield (QY) of 41.83%, an average size of 3.08 nm and demonstrated significant antifungal activity, effectively inhibiting fungal growth for up to 14 days. These findings suggest that CCDs have strong potential as a sustainable bioactive material.